ANALISIS KOMPARASI MODEL ALTMAN DAN MODEL SPRINGATE UNTUK MEMPREDIKSI FINANCIAL DISTRESS - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2020)
Analysis of the financial statements is very important for the company goes public to know the level of profitability (profit) and the level of risk or the soundness of a company. A public company listed on the Stock Exchange will be highly sensitive to external factors and may experience financial distress. The purpose of this study to analyze the differences in results between the 2 models of prediction models and the Altman Z-Score model of Springate on manufacturing companies listed in Indonesia Stock Exchange. This research is classified in comparative research. The analytical method used is a different test analysis using the Test Independent Sample T Test with a significance level of 0.05. The results of financial ratios Altman Z-Score models in 2013-2014 there were companies that remain in the position of bankruptcy are: IKAI, KRAS, AKKU, ESTI, HDTX, and KARW. Companies that remain in the Grey Area is BRPT and FPNI, while companies in 2013 are currently on Grey Area and then in 2014 in the position of bankruptcy is ADMG and RMBA. The results of financial ratios Springate in 2013-2014 models from almost all companies are in a state of bankruptcy is IKAI, KRAS, BRPT, AKKU, ADMG, ESTI, HDTX, KARW, and RMBA, only in 2014 there is a sample of companies that are in a healthy condition namely FPNI. Kata kunci: Financial Disress, Altman Z-Score, Springate.